2016
DOI: 10.22237/jmasm/1478002140
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Tests of Normality When Comparing Three Independent Samples

Abstract: This paper uses simulation to explore the performance of a two-stage procedure where a preliminary Shapiro-Wilk test is used to choose between the ANOVA and Kruskal-Wallis tests as a three-sample location test. The results suggest that the two-stage procedure actually seems to be preferable when conducting such location tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…To define a degree of connection between the percentage decrease in the number of pupils and stated variables in the Federation in the period from 2006 to 2016, the authors used the correlation method. Preliminary analyses for correlation (Rogerson 2001;McCarroll 2016;Pallant 2011) and the results of the Shapiro-Wilk and Kolmogorov-Smirnov tests (Lantz et al 2013) showed p<0.05, as did an analysis using Sperman's correlation coefficient (rho) to determine the degree and direction of relation between the assessed variables.…”
Section: Methodsmentioning
confidence: 99%
“…To define a degree of connection between the percentage decrease in the number of pupils and stated variables in the Federation in the period from 2006 to 2016, the authors used the correlation method. Preliminary analyses for correlation (Rogerson 2001;McCarroll 2016;Pallant 2011) and the results of the Shapiro-Wilk and Kolmogorov-Smirnov tests (Lantz et al 2013) showed p<0.05, as did an analysis using Sperman's correlation coefficient (rho) to determine the degree and direction of relation between the assessed variables.…”
Section: Methodsmentioning
confidence: 99%
“…Levene test was used to judge the homogeneity of variances, while the Shapiro-Wilk normality test was used to assess whether the data met the assumptions of the statistical approach, if the assumptions were not met, Kruskal-Wallis test ANOVA and Conover Multiple Comparison Test for Post hoc were used to demonstrate the significant differences between groups, P-values less than 0.05 were considered significant. (conover, 1999), (Lantz et al, 2016).…”
Section: B-count Of Cfu Of Ementioning
confidence: 99%
“…In contrast, to estimate the unconditional probability of a Type 1 error given a pre-test for normality, N samples (with mean differ-ence=0) are obtained and each is tested for normality. Samples that pass are subjected to a t-test, samples that do not are subjected to a non-parametric test, then: Lantz et al [32] used simulation to investigate pre-testing of three independent groups design. They used equal sample sizes in each group with three sizes: n=15, n=30 and n=60 per group.…”
Section: Pre-testing For Normality and Variance Heterogeneitymentioning
confidence: 99%
“…Finally, the three simulation studies, [32,45,48], did not explicitly consider the impact of outliers, although a recent paper by Derrick et al [15] identified problems for paired studies with extreme observations. They demonstrated that for small sample sizes a single extreme outlier could reduce the power of the standard t test, even if the outlier is in the same direction as the effect size of the other observations.…”
Section: Pre-testing For Normality and Variance Heterogeneitymentioning
confidence: 99%